PENGARUH PELATIHAN TERHADAP EFIKASI DIRI REMAJA SMA DALAM MEMBERIKAN RESUSITASI JANTUNG PARU - Ruing, Paulus Moses; Kurniawaty, Yuni; Wardhani, Iriene Kusuma (Sekolah Tinggi Ilmu Kesehatan Katolik St. Vincentius a Paulo Surabaya, 2023)
The increasing prevalence of out of cardiac arrest (OHCA) is related to the ineffectiveness of the help given and also influenced by self-efficacy. A high school student will have self-efficacy to become an active bystander if they are trained and willing to help the OHCA victim. The phenomenon encountered by the researcher was that the students in Dr. Soetomo Surabaya were unsure and did not dare to give CPR. The purpose of this study was to identify the effect of training on high school students' self-efficacy in administering CPR at Dr. Soetomo High School Surabaya. This study used a pre-experimental method with one-group pre- post test design. The samples of this study were adolescent students at Dr. Soetomo Surabaya as many 44 selected with simple random sampling technique. The research instrument used was the questionnaire on self-efficacy. The results of the Wilcoxon Signed Ranks statistical analysis showed that there was an effect of training on the self-efficacy of high school students in administering CPR at Dr. Soetomo High School Surabaya (p = 0,000). The training that uses the mannequin simulation method can affect adolescent students' self-efficacy in Dr. Soetomo High School Surabaya in administering CPR because it provides an experience like in the real world.